PENGARUH CURRENT RATIO DAN QUICK RATIO TERHADAP NET PROFIT MARGIN PADA PERUSAHAAN BASIC INDUSTRY AND CHEMICALS (JAKARTA ISLAMIC INDEX PERIODE 2016 - 2021) - Darmawan, Rayendra Arjun; Sissah, Sissah; Syahrizal, Ahmad (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study was to find out and analyze the effect of the current ratio and quick ratio on net profit margins in basic and chemical industry companies (Jakarta Islamic Index Period 2016 - 2021). In this study using quantitative methods and data analysis method used is panel data analysis. The samples used in this study were 10 companies with a total period of 6 years resulting in 60 data. The results showed that partially, the current ratio and quick ratio have a significant effect on the net profit margin. Simultaneously it shows that the current ratio and quick ratio have a significant influence on the net profit margin in basic and chemical industry companies listed on the JII for the 2016 – 2021 period. The results of the calculation of the coefficient of determination show that the current ratio and quick ratio variables have an influence on the net profit margin of 69.11% and the remaining 30.89% is influenced by other variables outside of this study.